Finite Heterogeneous Rate Constants for the Electrochemical Oxidation of VO2+ at Glassy Carbon Electrodes - Tichter, Tim; Schneider, Jonathan; Roth, Christina (Frontiers in Energy Research, 2020)
The electrochemical oxidation of VO2+ at planar glassy carbon electrodes is investigated via stationary and rotating linear sweep voltammetry as well as via chronoamperometry. It is demonstrated that introducing finite kinetic rate constants into the Butler-Volmer equation captures the experimentally observed concentration dependence of the ordinate intercept in Koutecký-Levich plots that cannot be explained by using the classical model. This new concept leads to a three-term Koutecký-Levich equation considering mass transport limitations, Butler-Volmer kinetics, as well as finite heterogeneous kinetics simultaneously. Based on these findings it is pointed out that stationary linear sweep voltammetry followed by an irreversible Randles-Ševčík analysis is not sufficient for deducing the electrode kinetics of the VO2+-oxidation. In contrast, it is verified experimentally and theoretically that a Tafel analysis will still provide reasonable values of k0 = 1.35 · 10−5 cm/s and α = 0.38, respectively. Finally, it is shown that introducing the concept of finite heterogeneous kinetics into the theory of stationary linear sweep voltammetry also explains the failure of the irreversible Randles-Ševčík relation leading to an extension of the classical model and providing insight into the electrochemical oxidation reaction of VO2+.